Design and implementation of a F-Commerce restaurant application - Khan, Mushfiquzzaman; Ahmed, Md. Faysal; Rahman, Kazi Mushfiqur (BARC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.